Kinematic assessment of an elastic‐core cervical disc prosthesis in one and two‐level constructs. Issue 4 (17th December 2018) - Guyer, Richard D.; Voronov, Leonard I.; Havey, Robert M.; Khayatzadeh, Saeed; Carandang, Gerard; Blank, Kenneth R.; Werner, Stephanie; Rubin, Josh; Padovani, Nick; Patwardhan, Avinash G.
Abstract : Introduction: Anterior cervical discectomy and fusion has been associated with the development of adjacent segment degeneration (ASD), with clinical incidence of approximately 3% per year. Cervical total disc arthroplasty (TDA) has been proposed as an alternative to prevent ASD. Hypotheses: TDA in optimal placement using an elastic‐core cervical disc (RHINE, K2M Inc., Leesburg, Virginia) will replicate natural kinematics and will improve with optimal vs anterior placement. Methods: Seven C3‐T1 cervical cadaver spines were tested intact first, then after one‐level TDA at C5‐C6 anterior placement, after TDA at C5‐C6 optimal placement, after two‐level TDA at C5‐C6 and C6‐C7 optimal placement, and finally after two‐level TDA at C5‐C6 lateral placement and C6‐C7 optimal placement. The specimens were subjected to: Flexion‐Extension moments (+1.5 Nm) with compressive preloads of 0 N and 150 N, lateral bending (LB) and axial rotation (AR) (+1.5 Nm) without preload. Results: C5‐C6 TDA in optimal placement resulted in a non‐significant increase in flexion‐extension ROM compared to intact under 0 N and 150 N preload ( P  > 0.05). Both LB and AR ROM decreased with arthroplasty ( P  < 0.01). O ptimal placement of C6‐C7 TDA resulted in an increase in flexion‐extension ROM with preload compared to intact ( P  < 0.05) while LB and AR ROM decreased with arthroplasty ( P  < 0.01). Conclusion: This six degree of freedom elastic‐core disc arthroplasty effectively restored flexion‐extension motion to intact levels. In LB the TDA maintained 42% ROM at C5‐C6 and 60% at C6‐C7. In AR 57% of the ROM was maintained at C5‐C6 and 70% at C6‐C7. These findings are supported by literature which shows cervical TDA results in restoration of approximately 50% ROM in LB and AR, which is a multifactorial phenomenon encompassing TDA design parameters and anatomical constraints. Anterior placement of this viscoelastic TDA device shows motion restoration similar to optimal placement suggesting its design may be less sensitive to suboptimal placement. Abstract : Kinematic evaluation of the Rhine cervical TDA was performed on C3‐T1 specimens. (Top Left) Experimental setup showing specimen with attached optoelectronic markers and follower load cables and guides. (Top Right) Anterior view of surgical implantation of Rhine TDA implanted at C5‐C6 and C6‐C7. Sub‐optimal placement of the TDA was evaluated at C5‐C6 by deliberate misplacement anteriorly and subsequently lateral to optimal position. (Bottom) Rhine cervical TDA showing flexible polymer core and keels for bone fixation. Cranial endplate is rendered as translucent to show internal details.